Measuring the Sociological Roots of the Emergence of the Phenomenon of Terrorism in Indonesia - Hidayatussalam; Misbahuddin; Kurniati; Abu Sahman Nasim (Formosa Journal of Sustainable Research, 2023)
This study aims to analyze efforts to measure sociologically the emergence of terrorism in Indonesia, as well as the development of terrorism and its prevention. As well as aiming to see in more detail the formation of the National Counterterrorism Agency (BNPT) has more comprehensive steps in preventing terrorism in Indonesia. This research uses descriptive qualitative. The research approach uses library research which obtains secondary data which includes literature books, laws and regulations, official documents and others. The results of this study indicate that, apart from making arrests, the BNPT also conducts research, coaching and integration of former terrorists into society, with a deradicalization program for both former perpetrators and potential potential perpetrators. Anti-terrorism campaigns are also carried out in schools. In this writing, the writer uses an empirical juridical approach and a sociological approach to understand the culture of society. The results of this paper are that terrorism has many dimensions, namely local dimensions, regional dimensions and global dimensions. To overcome the sociological roots of the emergence of terrorism in Indonesia, to overcome this requires the cooperation of all parties, the government, the community and the international world, because the action to overcome it is not by using repression so that it can violate human rights, but also using a socio-cultural approach by inviting all components including religious leaders so that the seeds of terrorism that exist in society can be minimized, and cutting the roots of its development, the growth of understanding of radicalism in common life